The Arabian Seas: Biodiversity, Environmental Challenges and Conservation Measures 2021
DOI: 10.1007/978-3-030-51506-5_8
|View full text |Cite
|
Sign up to set email alerts
|

Desert Dust as a Vector for Cyanobacterial Toxins

Abstract: Background: Brief Description of Deserts and Dust Storm FrontsDrylands, which make up 41-45% of the Earth's land area, are inhabited by 31% of the world's human population and are characterized by climatic forces which shape the physical environment and its biological life (UNCCD 2012;Prăvălie 2016; IPCC 2017;Maliva and Missimer, 2012). Although deserts were conceptualized singularly in the context of temperature maxima or lack of precipitation, aridity indices (AI) which take into consideration annual precip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 121 publications
0
3
0
Order By: Relevance
“…Drylands form 41%–45% of the land area, which is occupied by 31% of the world’s human population ( Metcalf et al., 2021 ). It has been shown that P deficiency restricts plant growth, especially in arid ecosystems, and P cycling is determined by both geochemical and biological factors.…”
Section: Plant Molecular Adaptations For P Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…Drylands form 41%–45% of the land area, which is occupied by 31% of the world’s human population ( Metcalf et al., 2021 ). It has been shown that P deficiency restricts plant growth, especially in arid ecosystems, and P cycling is determined by both geochemical and biological factors.…”
Section: Plant Molecular Adaptations For P Uptakementioning
confidence: 99%
“…It has been shown that P deficiency restricts plant growth, especially in arid ecosystems, and P cycling is determined by both geochemical and biological factors. The amount of water, soil type, P concentration, and plant diversity can be considered as aridity indices of desert environments ( Metcalf et al., 2021 ). Plants in desert conditions have evolved several morphological, metabolic, and physiological modifications, enabling the P acquisition from the dust (up to 30%).…”
Section: Plant Molecular Adaptations For P Uptakementioning
confidence: 99%
“…Coupled with the potential for dust production from a predominantly westerly wind, the possibility exists for crusts and other dried lakebed material to become airborne. This has the potential to adversely affect human populations, both short-and long-term [41].…”
Section: Introductionmentioning
confidence: 99%